Significance of bacterial vaginosis and periodontal infection as Predictors of preterm labor (Bangladesh Journal of Medical Science, 2016)
Aims: To study the relationship between bacterial vaginosis and periodontal infection in third trimester and preterm labor.Settings and Design: The present prospective case control study was conducted in the Department of Obstetrics and Gynaecology from January 2007 to June 2008, Government Medical College and Hospital, Sector 32 Chandigarh in collaboration with Department of Dentistry of the same hospital. Institutional Ethics Committee approval was taken, a written informed consent was taken from the patients.Methods and Material: Antenatal patients after 28 weeks of period of gestation and with singleton pregnancy attending OPD were included. Besides routine antenatal examination, screening and clinical examination for bacterial vaginosis, dental examination for periodontal infection was done. A total of 500 patients were enrolled for the study. Out of the 500 patients examined, 200 patients were randomly selected and divided into 4 groups with 50 women in each. Group 1 was the control group and the subjects were negative for bacterial vaginosis and periodontal infection. Group 2 was positive for periodontal infection. Group 3 was positive for bacterial vaginosis. Group 4 was positive for both bacterial vaginosis and periodontal infection. All these patients were followed up till their pregnancy outcomes.Statistical analysis used: A sample size of 50 patients in each group was calculated to conduct study with a power greater than 80% at a significance level of 5%. Data was analyzed using SPSS version 15.0 for Windows. Bacterial vaginosis and periodontal infection were separately correlated to the preterm birth and perinatal outcome. For ordinal data, groups were compared using Mann Whitney U-test, for continuous data groups were tested for normal distribution using the Kolmogorov-Smirnov test and for categorical data groups were compared using the chi-square test. p